A 5‐Year Prospective Study on Cone‐Anchored Implants in the Edentulous Maxilla. (26th February 2015) - Eerdekens, Liesbeth; Schols, Marlies; Coelst, Ludo; Quirynen, Marc; Naert, Ignace
Abstract: Purpose: To investigate dentist‐ as well as patient‐centered outcomes of the implant‐supported cone‐anchored removable prosthesis in the edentulous maxilla over 5 years. Materials and Methods: Ten patients, edentulous in the maxilla, received six Ti implants after which they were delayed loaded through a cone‐anchored removable prosthesis. Clinical parameters such as plaque and bleeding indices, PTV, implant success, marginal bone loss, device and prosthesis complications, and patient satisfaction (visual analogue scale) were collected at follow‐up visits scheduled 1, 3, 6, 12, 24, 36, and 60 months postprosthesis delivery. Results: After at least 5 years of follow‐up (mean: 63.7 months), 53/59 implants were rated successful, while two of 59 failed and one implant was kept sleeping. Mean marginal bone loss from prosthesis delivery until 1, 3, and 5 years, respectively, was; 0.15 (SD: 0.87), 0.36 (SD: 1.07), and 0.60 mm (SD: 1.12). The mean Periotest® values at baseline and 5 years did not differ significantly. After 1 year, a significant improvement in patient satisfaction was recorded compared with the old denture, and this remained stable over the 5‐year period. Conclusions: Cone‐anchored removable dental prostheses retained by secondary splinted implants offer a safe alternative for patients with an edentulous maxilla in need of more comfort. Dentist‐ as well as patient‐centered outcomes compete with reports using other prosthetic anchoring devices. Larger replica studies are encouraged to further validate this concept.